Parents' Evaluation of Early Childhood Newborn Parenting Education in Tertiary Healthcare Settings: A Cross-sectional Study - Shelina Bhamani; Aslam, Kiran; Shams, Misbah (JECCE, 2025)
Evidence has proved that early intervention, such as newborn parenting education programs, has a significant impact on child development. This study aims to explore the effectiveness of the newborn parenting education program in a tertiary care hospital in Karachi, Pakistan. A survey was conducted with parents who participated in a newborn parenting education program from October 2021 to December 2022. The sample size achieved was 287. The secondary data collected as part of the newborn inpatient ECD educator consult evaluation was also analyzed. Chi-square and Kruskal-Wallis tests were applied to check the significance of the program. The study findings showed that the mean ±SD score of overall course implementation was 4.2 ±0.7. The majority were very satisfied with the level of interaction with participants, 169 (58.9%), followed by 105 (36.6%), p<0.001 participants reported that they acquired new knowledge, 123 (42.9%) participant were extremely satisfied with the queries responded, 135 (47.0%) participants found the parenting material useful, and overall, they were extremely satisfied with the course implementation 116 (40.4%), p<0.001. However, future research is required to assess the effectiveness of parenting education programs across various levels of healthcare settings.